Fiscal management in federal democracies: Argentina and Brazil - Dillinger, William (1999)
This report investigates how these problems [déficit and decentralization] arose in Argentina and Brazil as they sought to decentralize in the 1980s and how each country dealt with them. We seek to understand the institutional arrangements -fiscal and political- that contributed to success or failure.